Kehidupan Sosial Masyarakat Pembuat Gula Merah di Desa Lembang Lohe Kecamatan Kajang Kabupaten Bulukumba - A. Nurfatimah Wardani (Rayhan Intermedia, 2018)
This study aims to find out: (1) Beginning of making brown sugar in Lembang Lohe Village, Kajang District; (2) the process of inheriting knowledge about making brown sugar; and (3) supporting and inhibiting factors in making brown sugar in the development of social life. This research uses qualitative data with descriptive type. Data collection was obtained through field research: observation, documentation and interviews involving 10 brown sugar makers. The results of the study show: (1) The beginnings of making brown sugar in Lembang Lohe Village carried out by their ancestors who used to make brown sugar only to fulfill their daily needs and not be traded. But in the last 20 years there has been a shift in business which used to only use coconut fruit, now producing sugar made from coconut sap; (2) the process of inheriting brown sugar is made by providing knowledge to his grandchildren early on, such as Angge'ba, tapping sap, tanrang appaenteng, setting up appallu golla stairs, cooking sugar to provide understanding of rituals or cooperating with brown sugar makers ; (3) The abundant wealth of natural resources and the cultural conditions of the people who still uphold mutual cooperation culture are the supporting factors in the business of making brown sugar. The inhibiting factors are the lack of human resources that can develop businesses in the modern era.